2016
DOI: 10.4992/jjpsy.87.15012
|View full text |Cite
|
Sign up to set email alerts
|

A sigh increases motivation for difficult and monotonous tasks: The effect of one-time voluntary brief exhalation on relief and achievement needs

Abstract: We tested possible intrapersonal effects of a sigh as a psychological "resetter/rebooter." Fifty-eight undergraduates were randomly assigned to a sigh or a normal exhalation (control) group. We asked participants on each task to model the experimenter demonstrating how to exhale air into a small plastic bag for breathing manipulation under the pretext that we were interested in the exhaled gas in stressful situations. Results revealed that the sigh group did not experience more relief (as shown by prolonged re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…According to Vlemincx et al [13], lungs stretch by sighing and ventilation efficiency rises. Also, according to Inoue et al [14], a sigh is a breath of at least twice the regular TV. A preceding study reported that such deep breaths help to reduce muscle tension and subjective stress-related feelings, and are closely related to balance in the autonomic nerve system and maintenance of homeostasis [15].…”
Section: Tidal Volumementioning
confidence: 99%
“…According to Vlemincx et al [13], lungs stretch by sighing and ventilation efficiency rises. Also, according to Inoue et al [14], a sigh is a breath of at least twice the regular TV. A preceding study reported that such deep breaths help to reduce muscle tension and subjective stress-related feelings, and are closely related to balance in the autonomic nerve system and maintenance of homeostasis [15].…”
Section: Tidal Volumementioning
confidence: 99%